2011
DOI: 10.1111/j.1541-0064.2010.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

The state of climate change adaptation in Canada's protected areas sector

Abstract: Recent suggestions by the World Commission on Protected Areas that conservation actions are likely to fail unless they are adjusted to take account of climate change, emphasize the need for protected areas agencies to begin mainstreaming climate change into policy, planning, and management. This article presents the results of a University of Waterloo and Canadian Council on Ecological Areas survey on the state of climate change adaptation in Canada's protected areas sector, including all federal, provincial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 44 publications
2
25
2
1
Order By: Relevance
“…Although our simulations did not include these finer resolutions, our results are consistent where comparisons were possible. Coincident aggregation patterns have also been reported in studies of the Indian mistletoe Taxillus tomentosus (Lemieux et al 2011).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although our simulations did not include these finer resolutions, our results are consistent where comparisons were possible. Coincident aggregation patterns have also been reported in studies of the Indian mistletoe Taxillus tomentosus (Lemieux et al 2011).…”
Section: Discussionsupporting
confidence: 57%
“…After comparing the models generated in this exercise, it is evident that incorporating colonization and extinction processes within a metapopulation framework sheds light on the importance that factors related to dispersal may have at finer scales for this species (Overton 1994, 1996, Aukema 2004, Lemieux et al 2011, and that more stable factors like climate either remain constant across resolutions or become more important in controlling the distribution of the species as the resolution becomes coarser.…”
Section: Discussionmentioning
confidence: 99%
“…These projections place Canada's boreal zone among the regions expected to experience the greatest climate change (Plummer et al 2006). Several authors have suggested that Canada's protected area system may be sensitive to climate change impacts Suffling and Scott 2002;Lemieux and Scott 2005;Lemieux et al 2011aLemieux et al , 2011b. Notably, the representation of boreal forests, in particular, is expected to decline as biomes shift north, given the current distribution of PPAs Lemieux and Scott 2005).…”
Section: Park and Protected Area Network In The Context Of Climate Cmentioning
confidence: 99%
“…3 Los estudios abordan las estrategias de adaptación implementadas desde las diferentes áreas de intervención, según modalidad turística y ámbito geográfico, realizando para los diferentes casos un balance de resultados (Becken y Hay, 2007;Gómez y Martínez, 2012;Gómez et al, 2014c;Lemieux et al, 2011;Martínez y Gómez, 2012a;Perry, 2000;Scott y McBoyle, 2007;Scott et al, 2003;Steiger, 2010). 4 Las investigaciones realizadas se han focalizado hasta el momento en dos aspectos básicos.…”
Section: Turismo E Información Climático-meteorológicaunclassified